2017
DOI: 10.1016/j.rvsc.2017.07.019
|View full text |Cite
|
Sign up to set email alerts
|

A new integrated approach to analyze bulk tank milk and raw milk filters for the presence of the E. coli serogroups frequently associated with VTEC status

Abstract: A new integrated approach to analyze bulk tank milk and raw milk filters for the presence of the E. coli serogroups frequently associated with VTEC status, Research in Veterinary Science (2017Science ( ), doi: 10.1016Science ( / j.rvsc.2017 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 37 publications
(4 reference statements)
1
17
0
Order By: Relevance
“…This study was designed to contribute to fill this gap by investigating the presence of pathogenic and CoEC in 149 isolates collected from BTM and RMF and their association with AMR pattern. The higher proportion of isolates from RMF, when compared to BTM confirmed the usefulness of this sampling in monitoring the presence of hazards at dairy herd level (Albonico et al, 2017;Murphy et al, 2005). Among all the isolates, 53 (35.6%) were classified as pathogenic while the other ones were classified as CoEC.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…This study was designed to contribute to fill this gap by investigating the presence of pathogenic and CoEC in 149 isolates collected from BTM and RMF and their association with AMR pattern. The higher proportion of isolates from RMF, when compared to BTM confirmed the usefulness of this sampling in monitoring the presence of hazards at dairy herd level (Albonico et al, 2017;Murphy et al, 2005). Among all the isolates, 53 (35.6%) were classified as pathogenic while the other ones were classified as CoEC.…”
Section: Discussionmentioning
confidence: 66%
“…Monitoring the raw milk at herd level showed to be a useful way to detect the presence of enteropathogenic strains and AMR bacteria, before being used to feed calves or to produce food for human consumption such as raw milk or raw milk products (Albonico et al, 2017;Berge et al, 2007). Besides the analysis of BTM, also RMF after milking showed to be a very useful tool to monitor the presence of hazards at milk and herd level (Albonico et al, 2017;Murphy et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, E. coli was found in all of the bulk tank milk samples (100%) in this study, none of the isolates had the STEC virulent gene. Albonico et al (2017) found the STEC O45 serotype in only 2 (2.9%) of 67 tank milk samples, as well as O157 and O145 in 1 (1.5%) sample. Another study found the stx gene in 32 (12.5%) of 255 bulk tank milk samples with 4 (12.5%) of these isolates were E. coli O157 and 6 (18.8%) were E. coli O26 serotypes (Trevisani et al, 2014).…”
Section: Discussionmentioning
confidence: 88%